Penerapan Metode Outbound Fun Game dalam Pembelajaran Bahasa Arab - Moh. Edi Komara (LISANIA: Journal of Arabic Education and Literature, 2017)
The quality of learning the Arabic language in Indonesia is still not perfect. It’s means that there are still many problems were found such as aspect of teacher, methods and media. Aspects of the method, teachers tend to retain the classical method than trying to explore a variety of methods that have been suggested by many researchers in learning Arabic. The trend is one of the main factors underlying the interest and student learning outcomes, learning methods of outbound fun games offers solutions with Alfresco-based learning concept which many contain elements of the game fun and can be felt directly by the student so that an increase in interest, motivation and student learning outcomes can be seen during the learning process.